2007
DOI: 10.2165/00019053-200725080-00007
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Year Prospective Cost-Effectiveness Analysis of Roflumilast for the Treatment of Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: Roflumilast increased the overall treatment costs of COPD, although the increase was partly offset by reductions in other forms of healthcare use. Roflumilast has the potential to be cost saving in patients with very severe COPD, due to a statistically significant reduction of exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Interpreting the costs per additional patient with a relevant improvement in SGRQ total score is more difficult, because no reference data are available and, up to now, only one study used this outcome in a CEA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting the costs per additional patient with a relevant improvement in SGRQ total score is more difficult, because no reference data are available and, up to now, only one study used this outcome in a CEA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it collected economic data prospectively within the trial, which permits the prospective assessment of value in terms of cost per QALY. Previous analyses of cost-effectiveness alongside clinical trials in COPD have only been able to report results in terms of cost per avoided exacerbation [23,24], which does not facilitate comparisons of results across disease areas (required for reimbursement decisions). QALY number results have previously been presented for COPD treatments, but based on economic modelling studies, which typically project treatment effects from short-term randomised controlled trials over the lifetime of patients [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the studies did not provide details of the productivity metric used to estimate productivity costs. Only two studies [43,53] explicitly reported using start and end dates for each absence spell. Most of the studies (46 %) that stated how productivity loss was estimated used a questionnaire.…”
Section: Methods Of Estimating Productivity Costs Using the Friction mentioning
confidence: 99%
“…When time was valued by using a wage rate for the value of work time forgone, studies used either a wage rate for the relevant age-sex dependent group (n = 19) or an average wage rate for all groups (n = 18). The exceptions were a weighted-average gross wage rate [43], a median wage rate [29], and the actual wage rate of respondents [36]. Seven studies reported using the age-group gender-based productivity cost per hour from the Dutch Costing Manual [52,54,60,[66][67][68].…”
Section: Methods Of Estimating Productivity Costs Using the Friction mentioning
confidence: 99%
See 1 more Smart Citation